Polymer Drilling Fluid with Micron-Grade Cenosphere for Deep Coal Seam - Peng Xu; Han-qiao Xiong; Xiao-lin Pu; Ju-quan Liu; Xing Liu (Journal of Chemistry)
Traditional shallow coal seam uses clean water, solid-free system, and foam system as drilling fluid, while they are not suitable for deep coal seam drilling due to mismatching density, insufficient bearing capacity, and poor reservoir protection effect. According to the existing problems of drilling fluid, micron-grade cenosphere with high bearing capacity and ultralow true density is selected as density regulator; it, together with polymer “XC + CMC” and some other auxiliary agents, is jointly used to build micron-grade polymer drilling fluid with cenosphere which is suitable for deep coal seam. Basic performance test shows that the drilling fluid has good rheological property, low filtration loss, good density adjustability, shear thinning, and thixotropy; besides, drilling fluid flow is in line with the power law rheological model. Compared with traditional drilling fluid, dispersion stability basically does not change within 26 h; settlement stability evaluated with two methods only shows a small amount of change; permeability recovery rate evaluated with Qinshui Basin deep coal seam core exceeds 80%. Polymer drilling fluid with cenosphere provides a new thought to solve the problem of drilling fluid density and pressure for deep coal seam drilling and also effectively improves the performance of reservoir protection ability.